Electrocardiogram metrics identify ionic current dysregulation relevant to atrial fibrillation. (3rd October 2022) - Dasi, A; Roy, A; Bueno-Orovio, A; Rodriguez, B
Abstract: Background: Personalisation of pharmacological treatment for atrial fibrillation (AF) is challenging. Pharmacological ionic current blockers such as digoxin or flecainide are commonly used, with caution given possible cardiotoxicity and proarrhythmia. Moreover, patients are stratified based on their associated heart disease rather than individual electrophysiological substrate, in part due to the inability for its non-invasive characterisation. Here we hypothesise that the ECG may contain information on key ionic currents regulating AF initiation and sustenance, and which would enable personalisation of pharmacological treatments to increase safety and efficacy. Purpose: To identify clinical ECG markers that reflect dysregulation of key ionic currents for AF using modelling and simulation in populations of whole-atria models without structural heart disease. Methods: Experimental data obtained from human AF and control patients was used to develop a virtual population of 200 whole-atria models (Figure, organ-level) with individual ionic profiles (Figure 1, bottom-left), including electrophysiological regional inhomogeneities (Figure 1, bottom-right). Modified-limb 12 lead ECGs were computed during sinus rhythm (Figure 1, body-surface-level) and biomarkers were quantified for the P and Ta-waves, such as duration, time-to-peak, decay, dispersion, amplitude and P-wave terminal force. Results: Simulated modified-limb ECG consistently reproduced the clinical ECG observed in human subjects, with an apparent Ta-wave inversion in lead II (Figure 1, body-surface-level). The inward rectified K+ current (IK1), known to be critical for AF, was the only ionic current associated with Ta-wave duration, showing an inversely proportional relationship (236±48 vs. 466±53 ms, IK1 up-regulation vs. down-regulation in lead V5; median ± interquartile range; P<0.001). Elevated IK1 additionally yield Ta-wave inversion in lead V5 and a higher Ta-wave magnitude in lead II (0.15±0.03 vs. 0.07±0.04 mV, IK1 up-regulation vs. down-regulation; P<0.001). However, Ta-wave magnitude showed a predominant relationship with the Na+/K+ pump (INaK), especially in the precordial leads (0.17±0.13 vs. 0.07±0.04 mV, INaK up-regulation vs. down-regulation in V5; P<0.001). Thus, the up-regulation of both currents led to very short, high-amplitude Ta-waves. While elevated IK1 additionally increased the P-wave terminal force (1.58±0.37 vs. 1.31±0.33 mV ms, IK1 up-regulation vs. down-regulation; P<0.001), a higher increase was observed for decreased fast Na+ current (INa) (1.35±0.17 vs. 1.86±0.30 mV ms, INa up-regulation vs. down-regulation; P<0.001). Conclusion: Ta-wave duration and amplitude are revealing of IK1 and INaK dysregulation, respectively, holding potential for improving cardiac safety and efficacy through a better stratification of AF patients for pharmacological treatment. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No. 860974